Isolating membrane, battery and electric device

CN119422280APending Publication Date: 2025-02-11CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049983.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing batteries easily form lithium dendrites during the charge and discharge process, causing internal short circuits and affecting the reliability and service life of the batteries. Moreover, the existing isolation membranes have insufficient electrolyte wettability and thermal stability.

Method used

A porous substrate is used as the basis of the isolation membrane, and a first coating and a second coating are coated on both sides. The first coating content is greater than 50% of the solid electrolyte, and the second coating content is greater than 50%. Inorganic particles that react with lithium dendrites reduce the probability of short circuit by promoting lithium ion transport and consuming lithium dendrites.

Benefits of technology

It improves the cycle performance and dynamic performance of the battery, extends the service life of the battery, reduces the probability of internal short circuit, and improves the heat resistance and mechanical strength of the isolation film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119422280A_ABST
    Figure CN119422280A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane, a battery and a power utilization device, the isolating membrane comprises a porous base material, and a first coating and a second coating which are respectively positioned on two surfaces of the porous base material, when the isolating membrane is used for the battery, the first coating faces a negative electrode, and the second coating faces a positive electrode; the first coating comprises first particles, the first particles comprise solid electrolyte, and the content of the first particles in the first coating is greater than 50 wt%; the second coating layer comprises second particles, the second particles comprise inorganic particles capable of reacting with lithium dendrites, and the content of the second particles in the second coating layer is greater than 50% by weight.
Need to check novelty before this filing date? Find Prior Art

Description

Separator, battery and electrical device Technical Field

[0001] The present application relates to an isolation film, a battery and an electrical device. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in consumer electronics, power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the application and promotion of batteries, their reliability and service life have received more and more attention. During the battery charging and discharging process, the dendrite problem on the negative electrode is one of the important reasons affecting the reliability and service life of the battery. How to slow down the growth of dendrites without affecting the electrochemical performance and / or kinetic performance of the battery is a technical problem that needs to be solved urgently. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art.

[0003] Summary of the Invention

[0004] The present application provides an isolation membrane, a battery and an electrical device, which can enable the battery to have good cycle performance and dynamic performance.

[0005] In a first aspect, the present application provides an isolation membrane, wherein the isolation membrane includes a porous substrate and a first coating and a second coating respectively located on two surfaces of the porous substrate. When used in a battery, the first coating faces the negative electrode and the second coating faces the positive electrode; the first coating includes first particles, the first particles include a solid electrolyte, and the content of the first particles in the first coating is greater than 50 weight%; the second coating includes second particles, the second particles include inorganic particles that can react with lithium dendrites, and the content of the second particles in the second coating is greater than 50 weight%.

[0006] The isolation membrane provided by the embodiments of the present application can have good heat resistance, mechanical strength, electrolyte infiltration characteristics and ion conductivity, and can effectively reduce the probability of internal short circuit of the battery, while also enabling the battery to have good cycle performance and kinetic performance.

[0007] In any embodiment of the present application, the content of the first particles in the first coating layer is greater than or equal to 60% by weight, optionally greater than or equal to 65% by weight, and more optionally 65-85% by weight. This enables the first coating layer to better promote lithium ion transport and uniform lithium ion flow, thereby helping to reduce the local formation of sharp lithium dendrites, further reducing the probability of internal short circuits in the battery, and improving the battery's cycling performance and dynamic performance.

[0008] In any embodiment of the present application, the content of the second particles in the second coating layer is greater than or equal to 60% by weight, optionally greater than or equal to 65% by weight, and more optionally 65-85% by weight. This enables the second coating layer to better counteract lithium dendrites, promptly consume lithium dendrites, and slow down or even prevent further growth of lithium dendrites, thereby further reducing the probability of internal short circuits in the battery and extending the cycle life of the battery.

[0009] In any embodiment of the present application, the first coating layer further includes third particles.

[0010] In any embodiment of the present application, the third particles include inorganic particles capable of reacting with lithium dendrites. When the first coating layer includes a small amount of inorganic particles capable of reacting with lithium dendrites, the first coating layer can react with, consume, and slow the growth of lithium dendrites without affecting the first coating layer's ability to promote lithium ion transport and uniform lithium ion flow, thereby further reducing the probability of internal short circuits in the battery and extending the battery's cycle life.

[0011] In any embodiment of the present application, the content of the third particles in the first coating layer is greater than 0 and less than or equal to 10 weight %, and can be optionally greater than 0 and less than or equal to 5 weight %.

[0012] In any embodiment of the present application, the volume distribution particle size Dv50 of the third particles is 0.05-3 μm, and can be optionally 0.1-1 μm.

[0013] In any embodiment of the present application, the solid electrolyte includes an inorganic solid electrolyte. Optionally, the conductivity of the inorganic solid electrolyte is greater than or equal to 10 -7 S / cm, more preferably greater than or equal to 10 -4 S / cm.

[0014] In any embodiment of the present application, the inorganic solid electrolyte includes one or more of an oxide-type inorganic solid electrolyte, a sulfide-type inorganic solid electrolyte, and a halide-type inorganic solid electrolyte.

[0015] In any embodiment of the present application, the oxide-type inorganic solid electrolyte includes one or more of a NASICON-type solid electrolyte, a garnet-type solid electrolyte, a perovskite-type solid electrolyte, and a LISICON-type solid electrolyte.

[0016] In any embodiment of the present application, the sulfide-type inorganic solid electrolyte includes one or more of a sulfide-type crystalline solid electrolyte and a sulfide glass-type solid electrolyte.

[0017] In any embodiment of the present application, the inorganic solid electrolyte includes lithium titanium phosphate (Lix Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate (Li x Al y Ge z (PO4)3, LAGP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate (Li x Al y Zr z (PO4)3, LAZP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum chromium phosphate (Li x Al y Cr z (PO4)3, LACP, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y type glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), lithium lanthanum tantalum oxide (Li5La3Ta2O 12 , LLTA), lithium zinc germanium oxide (Li 14 ZnGe4O 16 ), lithium thiargyrite electrolyte Li6PS5X (X includes one or more selected from Cl, Br, I), SiS2 type glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 type glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 、and one or more of their respective doped compounds.

[0018] Optionally, the inorganic solid electrolyte includes lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Tiz (PO4)3, LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate (Li x Al y Ge z (PO4)3, LAGP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate (Li x Al y Zr z [ (PO4)3, LAZP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum chromium phosphate (Li x Al y Cr z (PO4)3, LACP, 0 < x < 2, 0 < y < 1, 0 < z < 3), and one or more of their respective doped compounds. This can better promote lithium ion transport and uniform lithium ion flow, so that the deposition of lithium can be more uniform, reducing the local generation of sharp lithium dendrites, and further reducing the probability of internal short circuit in the battery, and improving the cycle performance and kinetic performance of the battery.

[0019] In any embodiment of the present application, the inorganic particles capable of reacting with lithium dendrites include inorganic ceramic particles.

[0020] [ In any embodiment of the present application, the inorganic ceramics include one or more of alumina, silica, silicon monoxide, iron oxide, iron oxide, cobalt monoxide, cobalt oxide, tin monoxide, tin dioxide, nickel oxide, iron phosphate, copper oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, aluminum nitride, silicon nitride, boron nitride, zirconium titanate, barium titanate, and their respective modified materials, and can be selected to include one or more of alumina, silica, silicon monoxide, cobalt monoxide, cobalt oxide, tin monoxide, tin dioxide, nickel oxide, iron phosphate, copper oxide, titanium oxide, and their respective modified materials. This can better react with lithium dendrites, timely consume lithium dendrites, slow down or even avoid the further growth of lithium dendrites, and further reduce the probability of internal short circuit in the battery and extend the cycle life of the battery.

[0021] In any embodiment of the present application, the volume distribution particle size Dv50 of the first particles is 0.05 - 3 μm, and can be selected as 0.1 - 1 μm. When the volume distribution particle size Dv50 of the first particles is within the above range, it is more conducive to promoting lithium ion transport and uniform lithium ion flow, and can better slow down or even inhibit the growth of lithium dendrites.

[0022] In any embodiment of the present application, the volume distribution particle size Dv50 of the second particles is 0.5-5 μm, optionally 1-3 μm. When the volume distribution particle size Dv50 of the second particles is within the above range, it can better react with the lithium dendrites, consume the lithium dendrites in a timely manner, and prevent further growth of the lithium dendrites.

[0023] In any embodiment of the present application, the first coating layer further includes one or more of a first binder, a first dispersant, and a first thickener.

[0024] In any embodiment of the present application, the mass ratio of the first particles to the first binder is 100:(1-25), and can be optionally 100:(5-22). An appropriate amount of the first binder can improve the heat resistance and uniformity of the first coating, effectively avoid problems such as powdering, and also help the isolation membrane have good ion conductivity.

[0025] In any embodiment of the present application, the mass ratio of the first particles to the first dispersant is 100:(1.0-3.5), and can be optionally 100:(1.2-2.5). An appropriate amount of the first dispersant can make the slurry disperse evenly, facilitate coating, and improve the film quality of the first coating.

[0026] In any embodiment of the present application, the mass ratio of the first particles to the first thickener is 100:(10-30), and can be optionally 100:(12-26). An appropriate amount of the first thickener can improve the stability of the slurry, facilitate coating, and improve the film quality of the first coating.

[0027] In any embodiment of the present application, the first binder includes one or more of vinylidene fluoride homopolymer and / or copolymer, sodium carboxymethyl cellulose, and styrene-butadiene rubber.

[0028] In any embodiment of the present application, the first dispersant includes one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymer, polyester block copolymer, polyethylene glycol type polyol, polyethyleneimine, and their respective derivatives.

[0029] In any embodiment of the present application, the first thickener includes one or more of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether.

[0030] In any embodiment of the present application, the second coating layer further includes one or more of a second binder, a second dispersant, and a second thickener.

[0031] In any embodiment of the present application, the mass ratio of the second particles to the second binder is 100:(1-25), and can be optionally 100:(8-22). An appropriate amount of the second binder can improve the heat resistance and uniformity of the second coating, effectively avoid problems such as powdering, and also help the separator have good ion conductivity.

[0032] In any embodiment of the present application, the mass ratio of the second particles to the second dispersant is 100:(0.5-4.0), and can be optionally 100:(1.0-2.0). An appropriate amount of the second dispersant can make the slurry disperse evenly, facilitate coating, and improve the film quality of the second coating.

[0033] In any embodiment of the present application, the mass ratio of the second particles to the second thickener is 100:(5-30), and can be optionally 100:(10-25). An appropriate amount of the second thickener can improve the stability of the slurry, facilitate coating, and improve the film quality of the second coating.

[0034] In any embodiment of the present application, the second binder includes one or more of vinylidene fluoride homopolymer and / or copolymer, sodium carboxymethyl cellulose, and styrene-butadiene rubber.

[0035] In any embodiment of the present application, the second dispersant includes one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymer, polyester block copolymer, polyethylene glycol type polyol, polyethyleneimine, and their respective derivatives.

[0036] In any embodiment of the present application, the second thickener includes one or more of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether.

[0037] In any embodiment of the present application, the surface density of the first coating is 9-12 g / m 2 , optional 10-11.5g / m 2 When the surface density of the first coating layer is within the above range, it helps to form a dense and uniform intermediate layer on the surface of the separator, better promoting lithium ion transmission and uniform lithium ion flow. It can also enable the separator to have a lower internal resistance, a shorter lithium ion transmission path and a higher lithium ion transmission rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0038] In any embodiment of the present application, the surface density of the second coating is 4-14 g / m 2 , optional 8-12g / m 2When the surface density of the second coating layer is within the above range, the second coating layer can better react with lithium dendrites, consume lithium dendrites in a timely manner, and prevent further growth of lithium dendrites; it can also make the separator have lower internal resistance, shorter lithium ion transmission path and higher lithium ion transmission rate, thereby making the battery have both good cycle performance and kinetic performance.

[0039] In any embodiment of the present application, the ratio of the thickness of the first coating layer to the thickness of the second coating layer is (0.2-5):1, and can be optionally (0.25-4):1. This can better play the role of the first coating layer and the second coating layer, which is beneficial for the first coating layer to better promote lithium ion transmission and uniform lithium ion flow, and is also beneficial for the second coating layer to better react with lithium dendrites, consume lithium dendrites in time, and slow down or even prevent further growth of lithium dendrites. This can further reduce the probability of internal short circuits in the battery and extend the cycle life of the battery.

[0040] In any embodiment of the present application, the thickness of the first coating layer is 1-7 μm, optionally 1.5-6 μm. When the thickness of the first coating layer is within this range, it helps form a dense and uniform intermediate layer on the surface of the separator, thereby better promoting lithium ion transport and uniform lithium ion flow. It also enables the separator to have a lower internal resistance, a shorter lithium ion transport path, and a higher lithium ion transport rate, thereby enabling the battery to have both good cycling performance and kinetic performance.

[0041] In any embodiment of the present application, the thickness of the second coating layer is 1-7 μm, optionally 1.5-6 μm. When the thickness of the second coating layer is within the above range, the second coating layer can better react with lithium dendrites, promptly consume lithium dendrites, and prevent further growth of lithium dendrites. It can also enable the separator to have a lower internal resistance, a shorter lithium ion transmission path, and a higher lithium ion transmission rate, thereby enabling the battery to have both good cycling performance and kinetic performance.

[0042] In any embodiment of the present application, the total thickness of the separator is 8-25 μm, optionally 8-18 μm. This allows the separator to have lower internal resistance, shorter lithium ion transmission path, and higher lithium ion transmission rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0043] In any embodiment of the present application, the porous substrate includes one or more of polyolefins, halogenated polyolefins, polyamides, polyesters, and their respective derivatives.

[0044] In any embodiment of the present application, the thickness of the porous substrate is 4-15 μm, and optionally 5-10 μm.

[0045] In any embodiment of the present application, the porosity of the isolation membrane is 40%-80%, and optionally 45%-70%.

[0046] In any embodiment of the present application, the transverse tensile strength of the isolation film is 1000-1500 kgf / cm 2 , optional 1100-1300kgf / cm 2 .

[0047] In any embodiment of the present application, the peel strength between the first coating layer of the isolation film and the porous substrate is 8.9-13.2 N / m, and can be optionally 9.1-11.8 N / m.

[0048] In any embodiment of the present application, the peel strength between the second coating layer of the isolation film and the porous substrate is 12.9-20.6 N / m, and optionally 13.5-17.8 N / m.

[0049] In any embodiment of the present application, the puncture strength of the isolation film is 9.60-11.50 N·μm -1 , optional 9.80-10.90N·μm -1 .

[0050] In any embodiment of the present application, the ionic conductivity of the isolation membrane at 25° C. is 1.40-2.50 mS·cm -1 , optional 1.60-2.15mS·cm -1 .

[0051] The second aspect of the present application provides a battery, including a battery cell and a box body, the battery cell including a positive electrode plate, a negative electrode plate and the isolation membrane of the first aspect of the present application, and the first coating of the isolation membrane faces the negative electrode plate, and the second coating of the isolation membrane faces the positive electrode plate.

[0052] In any embodiment of the present application, the battery cell includes at least one of a lithium-ion battery cell, a lithium metal battery cell, a negative electrode-free lithium metal battery cell, a lithium-sulfur battery cell, and a lithium-air battery cell.

[0053] A third aspect of the present application provides an electrical device comprising the battery of the second aspect of the present application.

[0054] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0056] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0057] FIG2 is an exploded schematic diagram of an embodiment of a battery cell of the present application.

[0058] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0059] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0060] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0061] FIG6 is a schematic diagram of an isolation film according to an embodiment of the present application.

[0062] FIG7 is a schematic diagram of an embodiment of an electric device including the battery of the present application as a power source.

[0063] In the accompanying drawings, which are not necessarily drawn to scale, reference numerals are as follows: 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate, 10 separator, 101 porous substrate, 102 first coating layer, 103 second coating layer. DETAILED DESCRIPTION

[0064] The following detailed description of the separator, battery, and electrical device disclosed herein will be described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0065] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0066] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0067] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0068] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0069] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0070] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0071] Unless otherwise specified, in this application, the terms "first", "second", "third", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.

[0072] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.

[0073] Unless otherwise stated, the values ​​of the various parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise stated, the test temperature of the parameters is 25°C.

[0074] The battery mentioned in the embodiments of the present application refers to a single physical module that includes one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack, etc. A battery cell is the smallest unit that makes up a battery, which can realize the function of charging and discharging alone. The present application has no special restrictions on the shape of the battery cell, which can be a cylinder, a rectangular parallelepiped or any other shape. Figure 1 is an example of a battery cell 5 with a rectangular parallelepiped structure. Multiple battery cells can be connected in series, in parallel or in mixed connection, and mixed connection refers to a mixture of series and parallel connection. In the embodiments of the present application, multiple battery cells can directly form a battery pack, or they can first form a battery module, and the battery modules can then form a battery pack.

[0075] A battery generally includes a casing for encapsulating one or more battery cells. The casing can prevent liquids or other foreign matter from affecting the charging or discharging of the battery cells. The casing can be a simple three-dimensional structure such as a single cuboid, cylinder, or sphere, or a complex three-dimensional structure composed of a combination of simple three-dimensional structures such as cuboids, cylinders, or spheres, and the embodiments of the present application do not limit this. The material of the casing can be an alloy material such as aluminum alloy, iron alloy, or a polymer material such as polycarbonate, polyisocyanurate foam plastic, or a composite material such as glass fiber and epoxy resin, and the embodiments of the present application do not limit this.

[0076] The battery cells mentioned in the embodiments of the present application may be at least one of lithium-ion battery cells, lithium metal battery cells, negative electrode-free lithium metal battery cells, lithium-sulfur battery cells, and lithium-air battery cells.

[0077] The battery cells provided in the embodiments of the present application include an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator positioned between the positive and negative electrode sheets. The electrode assembly may have a wound structure or a laminated structure, which is not limited in the embodiments of the present application.

[0078] The battery cell also includes an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte. The outer packaging can be a hard shell, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The soft package can be made of plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0079] As shown in Figure 2, the outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate. The base plate and side plates together form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening, thereby sealing the receiving cavity. The electrode assembly 52 is enclosed in the receiving cavity. The number of electrode assemblies 52 contained in a battery cell 5 can be one or more, and can be adjusted according to needs.

[0080] Battery cells can be assembled into battery modules, which can contain multiple battery cells. The specific number can be adjusted according to the application and capacity of the battery module. Figure 3 is a schematic diagram of an example battery module 4. As shown in Figure 3, in the battery module 4, multiple battery cells 5 can be arranged sequentially along the length of the battery module 4. Of course, they can also be arranged in any other manner. The multiple battery cells 5 can further be fixed using fasteners.

[0081] The battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 may be accommodated in the accommodation space.

[0082] The above-mentioned battery modules can also be assembled into a battery pack. The number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Figures 4 and 5 are schematic diagrams of a battery pack 1 as an example. As shown in Figures 4 and 5, the battery pack 1 may include a box and multiple battery modules 4 disposed in the box. The box includes an upper box 2 and a lower box 3. The upper box 2 is used to cover the lower box 3 and form an enclosed space for accommodating the battery modules 4. Multiple battery modules 4 can be arranged in the box in any manner.

[0083] As an important component of a battery cell, the performance of the separator is crucial to the performance of the battery. The separator is located between the positive and negative electrodes and mainly serves to prevent short circuits. The separators currently used in commercial batteries are usually porous membranes made of polyolefins (such as polyethylene, polypropylene, etc.). However, these separators have poor electrolyte wettability and thermal stability. In addition, as the number of charge and discharge cycles of the battery increases, lithium dendrites will form at the negative electrode interface. The continued growth of lithium dendrites will pierce the separator, causing internal short circuits, and in severe cases, even fires, explosions and other safety accidents.

[0084] Therefore, developing an isolation membrane with good thermal stability, excellent electrolyte wettability and high reliability is a technical problem that needs to be solved urgently in this field.

[0085] In view of this, the inventors improved the isolation membrane.

[0086] FIG6 is a schematic diagram of an isolation film according to an embodiment of the present application.

[0087] As shown in Figure 6, the separator 10 includes a porous substrate 101 and a first coating layer 102 and a second coating layer 103, respectively, located on the two surfaces of the porous substrate 101. When used in a battery, the first coating layer 102 faces the negative electrode, and the second coating layer 103 faces the positive electrode. The first coating layer 102 includes first particles, which include a solid electrolyte and the content of the first particles in the first coating layer is greater than 50% by weight. The second coating layer 102 includes second particles, which include inorganic particles capable of reacting with lithium dendrites and the content of the second particles in the second coating layer is greater than 50% by weight.

[0088] The first coating mainly includes a solid electrolyte. The solid electrolyte itself has high ionic conductivity and low electronic conductivity, so it can have good ionic conductivity and electronic insulation. When used in the first coating, it will not significantly increase the impedance of the isolation membrane, and can also reduce the transfer of electrons through the isolation membrane. In addition, the first coating faces the negative electrode and can form a dense and uniform intermediate layer on the surface of the isolation membrane, which promotes lithium ion transmission and uniform lithium ion flow, thereby inducing uniform lithium deposition, slowing down or even inhibiting the growth of lithium dendrites, and effectively reducing the local generation of sharp lithium dendrites, thereby reducing or even avoiding the problem of internal short circuit of the battery due to lithium dendrites piercing the isolation membrane.

[0089] The second coating faces the positive electrode and mainly includes inorganic particles that can react with lithium dendrites. Therefore, when the lithium dendrites generated on the surface of the negative electrode pierce the porous substrate during repeated charging and discharging, the second coating can react with the lithium dendrites, consume the lithium dendrites in time, and prevent the further growth of the lithium dendrites, thereby reducing or even avoiding the problem of lithium dendrites contacting the positive electrode and causing internal short circuit of the battery.

[0090] The first coating layer and the second coating layer are respectively located on both sides of the porous substrate, and there is no interface between the first coating layer and the second coating layer in the isolation membrane. Due to the different ionic conductivity of the first particles and the second particles, when the first coating layer and the second coating layer are located on the same side of the porous substrate, the concentration of lithium ions at the interface between the first coating layer and the second coating layer is different. The inventors have noticed that when the interface concentration difference is too large, it is easy to cause the formation of lithium dendrites, which in turn increases the probability of internal short circuit of the battery and reduces the service life of the battery. The isolation membrane provided by the embodiment of the present application does not have an interface between the first coating layer and the second coating layer, thereby avoiding the problem of lithium dendrites formed due to excessive interface concentration difference.

[0091] Porous substrates are highly hydrophobic, while electrolytes typically use polar solvents, resulting in poor electrolyte wettability and high ion transfer resistance for the porous substrate. The first and second coatings introduced into the separators provided in the embodiments of the present application have good compatibility with the electrolyte, thereby improving the separator's wettability with the electrolyte and reducing the separator's ion transfer resistance, thereby contributing to good cycling and kinetic performance of the battery. Furthermore, the first and second coatings introduced into the separators provided in the embodiments of the present application can also improve the separator's heat resistance and mechanical strength.

[0092] Therefore, the isolation membrane provided by the embodiments of the present application can have good heat resistance, mechanical strength, electrolyte infiltration characteristics and ion conductivity, and can effectively reduce the probability of internal short circuit of the battery, while also enabling the battery to have good cycle performance and kinetic performance.

[0093] In the first coating layer, the first particles include a solid electrolyte, and the content of the first particles is greater than 50% by weight. By making the first coating layer mainly include a solid electrolyte, it can promote lithium ion transmission and uniform lithium ion flow, thereby making lithium deposition more uniform, reducing the local generation of sharp lithium dendrites, and further reducing the probability of internal short circuit in the battery, while also allowing the battery to have good cycle performance and kinetic performance. When the content of the solid electrolyte in the first coating layer is too low, its effect on promoting lithium ion transmission and uniform lithium ion flow is poor, and thus the effect on slowing down lithium dendrite growth is poor, the probability of internal short circuit in the battery is high, and the cycle life of the battery is not excellent enough.

[0094] In some embodiments, the content of the first particles in the first coating layer may be greater than or equal to 60% by weight, optionally greater than or equal to 65% by weight, and more optionally greater than or equal to 68% by weight. This allows the first coating layer to better promote lithium ion transport and uniform lithium ion flow, thereby helping to reduce the local formation of sharp lithium dendrites, further reducing the probability of internal short circuits in the battery and improving the battery's cycling performance and kinetic performance. For example, the content of the first particles in the first coating layer may be 55-90 wt%, 58-90 wt%, 60-90 wt%, 62-90 wt%, 65-90 wt%, 68-90 wt%, 55-88 wt%, 58-88 wt%, 60-88 wt%, 62-88 wt%, 65-88 wt%, 68-88 wt%, 55-85 wt%, 58-85 wt%, 60-85 wt%, 62-85 wt%, 65-85 wt%, 68-85 wt%, 55-82 wt%, 58-82 wt%, 60-82 wt%, 62-82 wt%, 65-82 wt%, 68-82 wt%.

[0095] In the second coating layer, the second particles include inorganic particles that can react with lithium dendrites, and the content of the second particles is greater than 50% by weight. By making the second coating layer mainly include inorganic particles that can react with lithium dendrites, the second coating layer can consume the lithium dendrites in a timely manner, reducing the problem of further growth of lithium dendrites contacting the positive electrode and causing internal short circuit of the battery, thereby reducing the probability of internal short circuit of the battery and extending the cycle life of the battery. When the content of inorganic particles that can react with lithium dendrites is low, the second coating layer cannot consume the lithium dendrites in a timely manner, thereby causing the problem of lithium dendrites piercing the separator and causing internal short circuit of the battery, and the cycle life of the battery is not excellent enough.

[0096] In some embodiments, the content of the second particles in the second coating may be greater than or equal to 60% by weight, optionally greater than or equal to 65% by weight, and optionally greater than or equal to 68% by weight. This can enable the second coating to better react with lithium dendrites, consume lithium dendrites in a timely manner, slow down or even avoid the further growth of lithium dendrites, thereby further reducing the probability of internal short circuit of the battery and extending the cycle life of the battery. For example, the content of the second particles in the second coating may be 55-90% by weight, 58-90% by weight, 60-90% by weight, 62-90% by weight, 65-90% by weight, 55-88% by weight, 58-88% by weight, 68-90% by weight, 60-88% by weight, 62-88% by weight, 65-88% by weight, 68-88% by weight, 55-85% by weight, 58-85% by weight, 60-85% by weight, 62-85% by weight, 65-85% by weight, 68-85% by weight, 55-82% by weight, 58-82% by weight, 60-82% by weight, 62-82% by weight, 65-82% by weight, 68-82% by weight.

[0097] In some embodiments, the solid-state electrolyte may include an inorganic solid-state electrolyte. Optionally, the conductivity of the inorganic solid-state electrolyte may be greater than or equal to 10 -7 S / cm, more optionally greater than or equal to 10 -4 S / cm.

[0098] In some embodiments, the inorganic solid-state electrolyte may include one or more of an oxide-based inorganic solid-state electrolyte, a sulfide-based inorganic solid-state electrolyte, and a halide-based inorganic solid-state electrolyte.

[0099] In some embodiments, the oxide-based inorganic solid-state electrolyte may include one or more of a NASICON-type solid-state electrolyte, a garnet-type solid-state electrolyte, a perovskite-type solid-state electrolyte, and a LISICON-type solid-state electrolyte, and optionally includes a NASICON-type solid-state electrolyte. The NASICON-type solid-state electrolyte has the advantages of high conductivity and wide electrochemical window, and can better promote the transport of lithium ions and uniform the lithium ion flow, thereby making the deposition of lithium more uniform, reducing the local generation of sharp lithium dendrites, further reducing the probability of internal short circuit of the battery, and improving the cycle performance and kinetic performance of the battery.

[0100] In some embodiments, the sulfide-based inorganic solid-state electrolyte may include one or more of a sulfide-based crystalline solid-state electrolyte and a sulfide glass-based solid-state electrolyte.

[0101] As an example, the inorganic solid-state electrolyte may include lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Lix Al y Ti z (PO4)3, LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum titanium phosphate (Li x Al y Ge z (PO4)3, LAGP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate (Li x Al y Zr z (PO4)3, LAZP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate (Li x Al y Cr z (PO4)3, LACP, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y type glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), lithium lanthanum tantalum oxide (Li5La3Ta2O 12 , LLTA), lithium zinc germanium oxide (Li 14 ZnGe4O 16 ), lithium thiogermanate electrolyte Li6PS5X (X includes one or more selected from Cl, Br, I), SiS2 type glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, < z < 4), P2S5 type glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , and one or more of their respective doped compounds. Optionally, the inorganic solid electrolyte may include lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x )]]Al y Ti z (PO4)3, LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate (Li x Al y Ge z(PO4)3, LAGP, where 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate (Li x Al y Zr z (PO4)3, LAZP, where 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum chromium phosphate (Li x Al y Cr z (PO4)3, LACP, where 0 < x < 2, 0 < y < 1, 0 < z < 3), and one or more of their respective doped compounds. This can better promote lithium ion transport and uniform lithium ion flow, so that lithium deposition can be more uniform, reduce the local generation of sharp lithium dendrites, and further reduce the probability of internal short - circuit in the battery, and improve the cycle performance and kinetic performance of the battery.

[0102] Doped compounds are usually products obtained by doping other elements, such as metal elements, into a compound. The type of doped element is not particularly limited as long as it does not damage the main idea of this application.

[0103] For example, lithium titanium phosphate may include LiTi2(PO4)3, lithium aluminum titanium phosphate may include Li 1.3 Al 0.3 Ti 1.7 (PO4)3, lithium aluminum germanium phosphate may include Li 1.5 A1 0.5 Ge 1.5 (PO4)3, lithium lanthanum titanate may include Li 0.5 La 0.5 TiO3, the lithium thiophosphate electrolyte Li6PS5X may include Li6PS5Cl, Li6PS5Br.

[0104] In some embodiments, the inorganic particles capable of reacting with lithium dendrites may include inorganic ceramic particles.

[0105] In some embodiments, the inorganic ceramics may include one or more of alumina, silica, silicon monoxide, iron(III) oxide, iron(II,III) oxide, cobalt monoxide, cobalt(II,III) oxide, tin monoxide, tin dioxide, nickel oxide, iron phosphate, copper oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, aluminum nitride, silicon nitride, boron nitride, zirconium titanate, barium titanate, and their respective modified materials.

[0106] Alternatively, the inorganic ceramic may include one or more of aluminum oxide, silicon dioxide, silicon monoxide, cobalt monoxide, cobalt trioxide, tin monoxide, tin dioxide, nickel oxide, iron phosphate, copper oxide, titanium oxide, and their respective modified materials. This can better react with lithium dendrites, promptly consume them, and slow down or even prevent their further growth, thereby further reducing the probability of internal short circuits in the battery and extending the battery's cycle life.

[0107] Modification methods include physical modification and / or chemical modification. Chemical modification includes coupling agent modification (e.g., using silane coupling agents, titanate coupling agents, etc.), surfactant modification, polymer grafting modification, etc. Physical modification methods include mechanical dispersion, ultrasonic dispersion, high-energy treatment, etc.

[0108] In some embodiments, the volume distribution particle size Dv50 of the first particles may be 0.05-3 μm, optionally 0.05-2 μm, 0.08-2 μm, 0.1-2 μm, or 0.1-1 μm.

[0109] When the volume distribution particle size Dv50 of the first particles is within the above range, it is more conducive to promoting lithium ion transmission and uniform lithium ion flow, and can better slow down or even inhibit the growth of lithium dendrites. It can also effectively avoid the following situations: when the particle size of the first particles is too large, the slurry viscosity is large and uniformity cannot be guaranteed, making it difficult to evenly coat the porous substrate. In addition, during the coating process, the first particles are difficult to adhere to the surface of the porous substrate, and powder loss is likely to occur, resulting in poor coating effect and affecting the electrochemical performance of the battery. When the particle size of the first particles is too small, the first particles are more likely to enter the pores of the porous substrate during the coating process, which not only reduces the permeability of the isolation membrane, but also hinders the transmission of lithium ions, thereby increasing the capacity loss of the battery and shortening the cycle life.

[0110] In some embodiments, the volume distribution particle size Dv50 of the second particles may be 0.5-5 μm, optionally 0.5-4 μm, 0.8-4 μm, or 1-3 μm.

[0111] When the volume distribution particle size Dv50 of the second particles is within the above range, they can better react with lithium dendrites, consume lithium dendrites in time, and prevent further growth of lithium dendrites. Furthermore, the following situations can be effectively avoided: when the particle size of the second particles is too large, the slurry viscosity is high, uniformity cannot be guaranteed, and it is difficult to evenly coat the porous substrate. Furthermore, during the coating process, the second particles are difficult to adhere to the surface of the porous substrate, and powdering is likely to occur, resulting in poor coating effect and affecting the electrochemical performance of the battery. When the particle size of the second particles is too small, the second particles are more likely to enter the pores of the porous substrate during the coating process, which not only reduces the air permeability of the separator, but also loses the effect of the second coating layer in eliminating lithium dendrites, thereby increasing the capacity loss of the battery and shortening the cycle life.

[0112] In some embodiments, the first coating layer may further include third particles. Optionally, the content of the third particles in the first coating layer may be greater than 0 and less than or equal to 10 wt %, or may be greater than 0 and less than or equal to 5 wt %.

[0113] In some embodiments, the third particles may include inorganic particles capable of reacting with lithium dendrites. When the first coating layer includes a small amount of inorganic particles capable of reacting with lithium dendrites, this can help the first coating layer react with, consume, and slow the growth of lithium dendrites without affecting the first coating layer's ability to promote lithium ion transport and uniform lithium ion flow. This can further reduce the probability of internal short circuits in the battery and extend the battery's cycle life.

[0114] In some embodiments, the volume distribution particle size Dv50 of the third particles may be 0.05-3 μm, optionally 0.1-1 μm.

[0115] In some embodiments, the ratio of the thickness of the first coating layer to the thickness of the second coating layer may be (0.2-5):1, or optionally (0.25-4):1. This can better utilize the effects of the first coating layer and the second coating layer, helping the first coating layer to better promote lithium ion transmission and uniform lithium ion flow, and also helping the second coating layer to better react with lithium dendrites, promptly consume lithium dendrites, and slow down or even prevent further growth of lithium dendrites, thereby further reducing the probability of internal short circuits in the battery and extending the battery's cycle life.

[0116] In some embodiments, the first coating layer may further include a first binder. The present application does not particularly limit the type of the first binder. As examples, the first binder may include, but is not limited to, one or more of vinylidene fluoride homopolymer (PVDF) and / or copolymer, sodium carboxymethyl cellulose, and styrene-butadiene rubber.

[0117] In some embodiments, the mass ratio of the first particles to the first binder can be 100:(1-25), or optionally 100:(5-22). An appropriate amount of the first binder can improve the heat resistance and uniformity of the first coating, effectively prevent problems such as powdering, and contribute to the isolation membrane having good ion conductivity.

[0118] In some embodiments, the first coating layer may further include a first dispersant. The present application does not particularly limit the type of the first dispersant. For example, the first dispersant may include, but is not limited to, one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymers, polyester block copolymers, polyethylene glycol-type polyols, polyethyleneimine, and their respective derivatives. A derivative generally refers to a product derived from the replacement of hydrogen atoms or atomic groups in a polymer with other atoms or atomic groups.

[0119] In some embodiments, the mass ratio of the first particles to the first dispersant can be 100:(1.0-3.5), optionally 100:(1.2-2.5). An appropriate amount of the first dispersant can evenly disperse the slurry, facilitate coating, and improve the film quality of the first coating.

[0120] In some embodiments, the first coating layer may further include a first thickener. The present application does not particularly limit the type of the first thickener. As examples, the first thickener may include, but is not limited to, one or more of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether.

[0121] In some embodiments, the mass ratio of the first particles to the first thickener may be 100:(10-30), or optionally 100:(12-26). An appropriate amount of the first thickener can improve the stability of the slurry, facilitate coating, and improve the film quality of the first coating.

[0122] In some embodiments, the thickness of the first coating layer may be 1-7 μm, optionally 1.5-6 μm. When the thickness of the first coating layer is within the above range, it helps to form a dense and uniform intermediate layer on the surface of the isolation membrane, which better promotes lithium ion transmission and uniform lithium ion flow, thereby better inducing uniform lithium deposition, slowing down or even inhibiting the growth of lithium dendrites, and effectively reducing the local generation of sharp lithium dendrites, thereby reducing or even avoiding the problem of internal short circuit of the battery due to lithium dendrites piercing the isolation membrane. In addition, when the thickness of the first coating layer is within the above range, the isolation membrane can have a lower internal resistance, a shorter lithium ion transmission path and a higher lithium ion transmission rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0123] In some embodiments, the first coating may have an areal density of 9-12 g / m2 , optional 10-11.5g / m 2 . When the surface density of the first coating layer is within the above range, it helps to form a dense and uniform intermediate layer on the surface of the isolation membrane, which better promotes the transmission of lithium ions and the uniform flow of lithium ions, thereby better inducing the uniform deposition of lithium, slowing down or even inhibiting the growth of lithium dendrites, and effectively reducing the local generation of sharp lithium dendrites, thereby reducing or even avoiding the problem of internal short circuit of the battery due to lithium dendrites piercing the isolation membrane. In addition, when the surface density of the first coating layer is within the above range, the isolation membrane can have a lower internal resistance, a shorter lithium ion transmission path and a higher lithium ion transmission rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0124] In some embodiments, the second coating layer may further include a second binder. The present application does not particularly limit the type of the second binder. For example, the second binder may include, but is not limited to, one or more of vinylidene fluoride homopolymer and / or copolymer, sodium carboxymethyl cellulose, and styrene-butadiene rubber.

[0125] In some embodiments, the mass ratio of the second particles to the second binder can be 100:(1-25), or optionally 100:(8-22). An appropriate amount of the second binder can improve the heat resistance and uniformity of the second coating, effectively prevent problems such as powdering, and contribute to the separator having good ion conductivity.

[0126] In some embodiments, the second coating layer may further include a second dispersant. The present application does not particularly limit the type of the second dispersant. For example, the second dispersant may include, but is not limited to, one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymers, polyester block copolymers, polyethylene glycol-type polyols, polyethyleneimine, and their respective derivatives. A derivative generally refers to a product derived from the replacement of hydrogen atoms or atomic groups in a polymer with other atoms or atomic groups.

[0127] In some embodiments, the mass ratio of the second particles to the second dispersant can be 100:(0.5-4.0), optionally 100:(1.0-2.0). An appropriate amount of the second dispersant can evenly disperse the slurry, facilitate coating, and improve the film quality of the second coating.

[0128] In some embodiments, the second coating layer may further include a second thickener. The present application does not particularly limit the type of the second thickener. As examples, the second thickener may include, but is not limited to, one or more of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether.

[0129] In some embodiments, the mass ratio of the second particles to the second thickener may be 100:(5-30), or optionally 100:(10-25). An appropriate amount of the second thickener can improve the stability of the slurry, facilitate coating, and improve the film quality of the second coating.

[0130] In some embodiments, the thickness of the second coating layer may be 1-7 μm, optionally 1.5-6 μm. When the thickness of the second coating layer is within the above range, the second coating layer can better react with lithium dendrites, consume lithium dendrites in a timely manner, and prevent further growth of lithium dendrites, thereby effectively reducing or even preventing the problem of lithium dendrites contacting the positive electrode and causing internal short circuits in the battery. In addition, when the thickness of the second coating layer is within the above range, the separator can have a lower internal resistance, a shorter lithium ion transmission path, and a higher lithium ion transmission rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0131] In some embodiments, the second coating may have an areal density of 4-14 g / m 2 , optional 8-12g / m 2 . When the surface density of the second coating layer is within the above range, the second coating layer can better react with lithium dendrites, consume lithium dendrites in time, and prevent further growth of lithium dendrites, thereby effectively reducing or even preventing the problem of lithium dendrites contacting the positive electrode and causing internal short circuits in the battery. In addition, when the surface density of the second coating layer is within the above range, the separator can have a lower internal resistance, a shorter lithium ion transmission path, and a higher lithium ion transmission rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0132] In some embodiments, the porous substrate may have a thickness of 4-15 μm, optionally 5-10 μm.

[0133] In some embodiments, the porous substrate may include, but is not limited to, one or more of polyolefins (e.g., polyethylene, polypropylene, etc.), halogenated polyolefins (e.g., polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, etc.), polyamides, polyesters (e.g., polyethylene terephthalate, etc.), and their respective derivatives.

[0134] Derivatives usually refer to products derived from the replacement of hydrogen atoms or atomic groups in polymers by other atoms or atomic groups.

[0135] In some embodiments, the porous substrate may have a weight average molecular weight of 100,000 to 1,000,000.

[0136] The weight average molecular weight of the porous substrate has a well-known meaning in the art and can be measured using methods known in the art, for example, by gel permeation chromatography (GPC).

[0137] In some embodiments, the total thickness of the separator may be 8-25 μm, optionally 8-18 μm, thereby enabling the separator to have lower internal resistance, shorter lithium ion transport path, and higher lithium ion transport rate, thereby enabling the battery to have both good cycle performance and kinetic performance.

[0138] In some embodiments, the porosity of the isolation membrane may be 40%-80%, and optionally 45%-70%, thereby helping the isolation membrane to have good air permeability and high ion transmission capacity.

[0139] The porosity of the separator has a well-known meaning in the art and can be measured using methods known in the art, for example, according to the standard GB / T 36363-2018.

[0140] In some embodiments, the transverse direction (TD) tensile strength of the separator may be 1000-1500 kgf / cm 2 , optional 1100-1300kgf / cm 2 This can improve the reliability of the battery.

[0141] The transverse tensile strength of a separator has a meaning generally known in the art and can be measured using methods known in the art. For example, the test can be performed in accordance with standard GB / T 36363-2018. During the test, the tensile rate can be 50 mm / min.

[0142] In some embodiments, the peel strength between the first coating layer of the isolation film and the porous substrate may be 8.9-13.2 N / m, and optionally 9.1-11.8 N / m.

[0143] In some embodiments, the peel strength between the second coating layer of the isolation film and the porous substrate may be 12.9-20.6 N / m, and optionally 13.5-17.8 N / m.

[0144] The separator has high peel strength, thereby improving the reliability of the battery.

[0145] The peel strength of a separator has a well-known meaning in the art and can be measured using methods known in the art. For example, it can be tested with reference to the standard GB / T 36363-2018.

[0146] In some embodiments, the puncture strength of the isolation film can be 9.60-11.50 N·μm -1 , optional 9.80-10.90N·μm -1 This can improve the reliability of the battery.

[0147] The puncture strength of a separator has a well-known meaning in the art and can be measured using methods known in the art. For example, the test can be performed in accordance with the standard GB / T 36363-2018.

[0148] In some embodiments, the ionic conductivity of the isolation membrane at 25°C may be 1.40-2.50 mS·cm -1 , optional 1.60-2.15mS·cm -1 . This can improve the battery's cycle performance and kinetic performance.

[0149] The ionic conductivity of the isolation membrane can be obtained through electrochemical impedance spectroscopy experiments. For example, the isolation membrane can be cut into discs of a certain area, dried, and placed between two stainless steel electrodes. After absorbing a sufficient amount of electrolyte, it is sealed to form a button battery and an electrochemical impedance spectroscopy experiment is performed. The resistance Rs of different isolation membrane layers n is measured using the confined symmetric battery electrochemical impedance spectroscopy method as the isolation membrane resistance. The slope k (corresponding to the resistance of a single-layer isolation membrane) is obtained by plotting Rs and n. The ionic conductivity of the isolation membrane is calculated based on the resistance of the single-layer isolation membrane, the area of ​​the isolation membrane, and the thickness of the isolation membrane (single-layer thickness).

[0150] The volume distribution particle size Dv50 of the particles is well known in the art and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer (e.g., Master Size 3000) in accordance with GB / T 19077-2016.

[0151] [Method for preparing isolation film]

[0152] An embodiment of the present application also provides a method for preparing an isolation film.

[0153] The preparation method includes the following steps: providing a porous substrate; providing a first coating slurry and a second coating slurry, wherein the first coating slurry includes first particles, the first particles include a solid electrolyte, and the content of the first particles in the first coating after drying is greater than 50 weight%, and the second coating slurry includes second particles, the second particles include inorganic particles that can react with lithium dendrites, and the content of the second particles in the second coating after drying is greater than 50 weight%; coating the first coating slurry and the second coating slurry on two surfaces of the porous substrate respectively, and obtaining an isolation membrane after drying.

[0154] In some embodiments, the first coating slurry may further include third particles.

[0155] In some embodiments, the first coating slurry may further include one or more of a first binder, a first dispersant, and a first thickener.

[0156] In some embodiments, the step of providing a first coating slurry may include the following steps: adding first particles, a first dispersant, and optional third particles to a first solvent for primary dispersion to obtain a primary dispersion solution; adding a first thickener to the obtained primary dispersion solution for secondary dispersion to obtain a secondary dispersion solution; adding a first binder to the obtained secondary dispersion solution and stirring evenly to obtain a first coating slurry.

[0157] Optionally, in the step of providing the first coating slurry, the first solvent may include one or more of deionized water, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0158] Optionally, in the step of providing the first coating slurry, the primary dispersion process may be ultrasonic dispersion. Optionally, the ultrasonic dispersion time is more than 2 hours.

[0159] Optionally, in the step of providing the first coating slurry, stirring is required during the secondary dispersion process. For example, the stirring speed may be 500-1200 rpm and the stirring time may be 0.5-1.5 h.

[0160] Optionally, in the step of providing the first coating slurry, after adding the first binder to the obtained secondary dispersion solution, the mixture may be stirred at a rotation speed of 500-1200 rpm for 0.5-1.5 h.

[0161] In some embodiments, the solid content of the first coating slurry may be 30%-50%, and optionally 34%-45%, which facilitates coating.

[0162] In some embodiments, the second coating slurry may further include one or more of a second binder, a second dispersant, and a second thickener.

[0163] In some embodiments, the step of providing a second coating slurry may include the following steps: adding second particles and a second dispersant to a second solvent for primary dispersion to obtain a primary dispersion solution; adding a second thickener to the obtained primary dispersion solution for secondary dispersion to obtain a secondary dispersion solution; adding a second binder to the obtained secondary dispersion solution and stirring evenly to obtain a second coating slurry.

[0164] Optionally, in the step of providing the second coating slurry, the second solvent may include one or more of deionized water, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0165] Optionally, in the step of providing the second coating slurry, the primary dispersion process may be ultrasonic dispersion. Optionally, the ultrasonic dispersion time is more than 2 hours.

[0166] Optionally, in the step of providing the second coating slurry, stirring is required during the secondary dispersion process. For example, the stirring speed may be 500-1200 rpm and the stirring time may be 0.5-1.5 h.

[0167] Optionally, in the step of providing the second coating slurry, the second binder is added to the obtained secondary dispersion solution, and then the mixture is stirred at a rotation speed of 500-1200 rpm for 0.5-1.5 hours.

[0168] In some embodiments, the solid content of the second coating slurry is 30%-50%, and optionally 34%-45%, which facilitates coating.

[0169] In some embodiments, when the first coating slurry and the second coating slurry are respectively coated on two surfaces of the porous substrate and then dried, the drying temperature may be 60-120°C.

[0170] In some embodiments, the coating method of the first coating slurry and the second coating slurry can be transfer coating, rotary spray coating, dip coating, wire rod coating, etc., which is not limited in the embodiments of the present application.

[0171] Some parameters such as raw materials and their contents used in the preparation method of the isolation membrane provided in the embodiment of the present application can refer to the isolation membrane of the first aspect of the embodiment of the present application, and will not be repeated here.

[0172] Unless otherwise specified, all raw materials used in the method for preparing the isolation membrane provided in the embodiments of the present application can be obtained commercially.

[0173] [Positive electrode]

[0174] The structure and composition of the positive electrode plate can be selected according to the type of battery cell, and the embodiments of the present application are not limited thereto.

[0175] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector has two opposing surfaces in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.

[0176] The positive electrode active material includes a material capable of extracting and inserting lithium ions. For example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates, layered metal chalcogenides, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium titanium oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.

[0177] In some embodiments, in order to further improve the energy density of the battery, the positive electrode active material may include a general formula of Li a Ni b Co c M d O e D f One or more lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes one or more of Ge, Mo, Sn, Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and D includes one or more of N, F, S and Cl.

[0178] As an example, the positive electrode active material may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 2 Mn 1 / 2 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3One or more of S2.

[0179] The modified compounds of the above-mentioned positive electrode active materials may be used to perform doping modification and / or surface coating modification on the positive electrode active materials.

[0180] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. For example, the positive electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0181] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. This application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylic resin, and polyethylene oxide.

[0182] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0183] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying it, and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0184] [Negative electrode]

[0185] The structure and composition of the negative electrode plate can be selected according to the type of battery cell, and the embodiments of the present application are not limited thereto.

[0186] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material, which includes a material capable of extracting and inserting active ions. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.

[0187] The negative electrode active material may be any known negative electrode active material in the art. For example, the negative electrode active material may include, but is not limited to, one or more of carbon-based materials, silicon-based materials, tin-based materials, and lithium titanate. Carbon-based materials may include one or more of natural graphite, artificial graphite, soft carbon, hard carbon, pyrolytic carbon, coke, glassy carbon, a sintered product of an organic polymer compound, and mesophase carbon microbeads. Silicon-based materials may include one or more of elemental silicon, silicon oxide, a silicon-carbon complex, a silicon-nitrogen complex, and a silicon alloy. Tin-based materials may include one or more of elemental tin, tin oxide, and a tin alloy.

[0188] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0189] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As examples, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0190] In some embodiments, the negative electrode film layer may further include other additives, such as thickeners, sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.

[0191] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0192] The negative electrode film layer is typically formed by coating the negative electrode slurry onto the negative electrode current collector, drying it, and cold pressing it. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0193] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate further includes a protective layer covering the surface of the negative electrode film layer.

[0194] In some embodiments, the negative electrode plate may not include materials capable of extracting and embedding active ions, such as graphite. For example, in some embodiments, the negative electrode plate may include a lithium plate or a lithium alloy plate; in other embodiments, the negative electrode plate includes a mesh or foam-like three-dimensional skeleton layer, such as copper foam (or copper alloy), nickel foam (or nickel alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, etc.

[0195] [Electrolyte]

[0196] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.

[0197] As an example, the electrolyte salt may include, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0198] In some embodiments, the concentration of the electrolyte salt may be 0.3 mol / L or more, and may be 0.7 mol / L or more. The concentration of the electrolyte salt may be 4 mol / L or less, and may be 2.5 mol / L or less, or 1.7 mol / L or less.

[0199] The solvent may include one or more of esters (eg, carbonates, phosphates, carboxylates, sulfates, sulfonates, etc.), ethers, sulfones, nitriles, and the like.

[0200] For example, when the battery cell is a lithium-ion battery cell, as an example, the solvent may include but is not limited to one or more of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), tetraethylene glycol dimethyl ether (TEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), trimethyl phosphate, and 3-methoxypropionitrile.

[0201] For example, when the battery cell is a lithium metal battery cell or a negative electrode-free lithium metal battery cell, the solvent may include an ether solvent and / or a fluoroether solvent, such as dimethyl ether tetraethylene glycol (TEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), H(CF2)2OCH3, C4F9OCH3, H(CF2)2OCH2CH3, H(CF2)2OCH2CF3, H(CF2)2CH2O(CF2)2H, CF3CHFCF2OCH3, CF3CHFCF2OCH2CH3, 2-trifluoromethylhexafluoropropyl methyl ether, 2-trifluoromethylhexafluoropropyl ethyl ether, 2 - one or more of trifluoromethyl hexafluoropropyl propyl ether, 3-trifluoromethyl octafluorobutyl methyl ether, 3-trifluoromethyl octafluorobutyl ethyl ether, 3-trifluoromethyl octafluorobutyl propyl ether, 4-trifluoromethyl decafluoropentyl methyl ether, 4-trifluoromethyl decafluoropentyl ethyl ether, 4-trifluoromethyl decafluoropentyl propyl ether, 5-trifluoromethyl dodecafluorohexyl methyl ether, 5-trifluoromethyl dodecafluorohexyl ethyl ether, 5-trifluoromethyl dodecafluorohexyl propyl ether, 6-trifluoromethyl tetradecafluoroheptyl methyl ether, 6-trifluoromethyl tetradecafluoroheptyl ethyl ether, 6-trifluoromethyl tetradecafluoroheptyl propyl ether, 7-trifluoromethyl hexafluorooctyl methyl ether, 7-trifluoromethyl hexadecafluorooctyl ethyl ether, and 7-trifluoromethyl hexadecafluorooctyl propyl ether.

[0202] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0203] The embodiments of the present application also provide an electrical device, which includes the battery of the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0204] The electrical device can select a specific type of battery according to its usage requirements, such as a battery cell, a battery module or a battery pack.

[0205] Figure 7 is a schematic diagram of an exemplary electrical device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's high power and high energy density requirements, a battery pack or battery module can be used as a power source.

[0206] As another example, an electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a battery cell as a power source.

[0207] An Shili

[0208] The following examples further describe the present disclosure. These examples are intended for illustrative purposes only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise indicated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and used without further processing. All instruments used in the examples are commercially available.

[0209] The isolation membranes of Examples 1-27 were all prepared according to the following method.

[0210] Preparation of porous substrates

[0211] A 7 μm thick polyethylene porous membrane was washed with ethanol or acetone, dried at 60° C., flattened, and then plasma treated for 4 minutes to obtain a porous substrate for standby use.

[0212] Preparation of the first coating slurry

[0213] The first particles, third particles, first dispersant acrylic block copolymer and first solvent NMP shown in Table 1 were mixed and ultrasonically dispersed in an ultrasonic cleaning machine for 2 hours to obtain a primary dispersion solution. The first thickener sodium hydroxymethyl cellulose was added to the obtained primary dispersion solution for secondary dispersion to obtain a secondary dispersion solution. The stirring speed was 1100 rpm and the stirring time was 1 hour. The first binder PVDF was added to the obtained secondary dispersion solution and stirred at 900 rpm for 60 minutes to obtain the first coating slurry. In Examples 1-27, the mass ratios of the first particles, the third particles, the first binder, the first thickener and the first dispersant are shown in Table 1. In Table 1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 is abbreviated as LATP, LiTi2(PO4)3 is abbreviated as LTP, Li7La3Zr2O 12 Abbreviated as LLZO.

[0214] Preparation of the second coating slurry

[0215] The second particles shown in Table 1, the second dispersant acrylic block copolymer, and the second solvent NMP were mixed and ultrasonically dispersed in an ultrasonic cleaner for 2 hours to obtain a primary dispersion solution. The second thickener sodium hydroxymethyl cellulose was added to the obtained primary dispersion solution for secondary dispersion to obtain a secondary dispersion solution. The stirring speed was 1100 rpm and the stirring time was 1 hour. The second binder PVDF was added to the obtained secondary dispersion solution and stirred at 900 rpm for 60 minutes to obtain a second coating slurry. In Examples 1-27, the mass ratios of the second particles, the second binder, the second thickener, and the second dispersant are shown in Table 1.

[0216] Preparation of isolation membrane

[0217] The first coating slurry and the second coating slurry were coated on both sides of the porous substrate by wire bar coating, and vacuum dried at 60° C. for 30 minutes to obtain a separator. In Examples 1-27, the thickness of the first coating and the second coating are shown in Table 1.

[0218] Comparative Example 1

[0219] Preparation of porous substrates

[0220] A 7 μm thick polyethylene porous membrane was washed with ethanol or acetone, dried at 60° C., flattened, and then plasma treated for 4 minutes to obtain a porous substrate for standby use.

[0221] Preparation of coating slurry

[0222] Li 1.3 Al 0.3 Ti 1.7 (PO4)3, dispersant acrylic block copolymer and solvent NMP were mixed and ultrasonically dispersed in an ultrasonic cleaning machine for 2 hours to obtain a primary dispersion solution. Thickener sodium hydroxymethyl cellulose was added to the obtained primary dispersion solution for secondary dispersion to obtain a secondary dispersion solution. The stirring speed was 1100 rpm and the stirring time was 1 hour. Binder PVDF was added to the obtained secondary dispersion solution and stirred at 900 rpm for 60 minutes to obtain a coating slurry. 1.3 Al 0.3 Ti 1.7 The mass ratio of (PO4)3, binder, thickener and dispersant is 100:25.0:2.5:30.0.

[0223] Preparation of isolation membrane

[0224] The coating slurry was applied to both sides of the porous substrate by wire rod coating and dried in vacuum at 60° C. for 30 minutes to obtain a separator. The thickness of the coating on both sides of the porous substrate was 4 μm.

[0225] Comparative Example 2

[0226] Preparation of porous substrates

[0227] A 7 μm thick polyethylene porous membrane was washed with ethanol or acetone, dried at 60° C., flattened, and then plasma treated for 4 minutes to obtain a porous substrate for standby use.

[0228] Preparation of coating slurry

[0229] SiO particles, a dispersant (acrylic block copolymer), and a solvent (NMP) were mixed and ultrasonically dispersed in an ultrasonic cleaner for 2 hours to obtain a primary dispersion solution. A thickener (sodium hydroxymethyl cellulose) was added to the primary dispersion solution for secondary dispersion, stirring at 1100 rpm for 1 hour. A binder (PVDF) was added to the secondary dispersion solution, and the mixture was stirred at 900 rpm for 60 minutes to obtain a coating slurry. The mass ratio of SiO particles, binder, thickener, and dispersant was 100:25.0:2.5:30.0.

[0230] Preparation of isolation membrane

[0231] The coating slurry was applied to both sides of the porous substrate by wire rod coating and dried in vacuum at 60° C. for 30 minutes to obtain a separator. The thickness of the coating on both sides of the porous substrate was 4 μm.

[0232] Comparative Example 3

[0233] Preparation of porous substrates

[0234] A 7 μm thick polyethylene porous membrane was washed with ethanol or acetone, dried at 60° C., flattened, and then plasma treated for 4 minutes to obtain a porous substrate for standby use.

[0235] Preparation of the first coating slurry

[0236] The first particle Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (volume distribution particle size Dv50 is 0.5μm), the first dispersant acrylic block copolymer and the first solvent NMP are mixed and ultrasonically dispersed in an ultrasonic cleaner for 2 hours to obtain a primary dispersion solution. The first thickener sodium hydroxymethyl cellulose is added to the obtained primary dispersion solution for secondary dispersion to obtain a secondary dispersion solution. The stirring speed is 1100rpm and the stirring time is 1h. The first binder PVDF is added to the obtained secondary dispersion solution and stirred at 900rpm for 60min to obtain a first coating slurry. The mass ratio of the first particles, the first binder, the first thickener, and the first dispersant is 100:65:5:75.

[0237] Preparation of the second coating slurry

[0238] Mix the second SiO particles (volume distribution particle size Dv50: 1 μm), the second dispersant acrylic block copolymer, and the second solvent NMP, and ultrasonically disperse them in an ultrasonic cleaner for 2 hours to obtain a primary dispersion solution. Add the second thickener sodium hydroxymethyl cellulose to the resulting primary dispersion solution for secondary dispersion, stirring at 1100 rpm for 1 hour. Add the second binder PVDF to the resulting secondary dispersion solution, and stir at 900 rpm for 60 minutes to obtain a second coating slurry. The mass ratio of the second particles, second binder, second thickener, and second dispersant is 100:65:5:75.

[0239] The first coating slurry and the second coating slurry were coated on both sides of the porous substrate by wire rod coating, and vacuum dried at 60° C. for 30 minutes to obtain a separator. The thickness of the first coating and the second coating were both 4 μm.

[0240] In the above Examples 1-27 and Comparative Examples 1-3, when the separator is used in a battery, the first coating layer faces the negative electrode and the second coating layer faces the positive electrode.

[0241] Comparative Example 4

[0242] The preparation method of the separator is the same as that of Example 1, except that when the separator is used in a battery, the first coating layer of the separator prepared in Example 1 is arranged to face the positive electrode, and the second coating layer is arranged to face the negative electrode.

[0243] Performance Testing

[0244] (1) Transverse tensile strength test of isolation film

[0245] Test the transverse tensile strength of the separator film according to GB / T 36363-2018. Cut the separator film into samples with a width of 10 mm and a length of 150 mm (with the length direction parallel to the transverse direction of the separator film) for testing. The testing instrument can be a universal tensile testing machine with a tensile rate of 50 mm / min. Six or more separator film samples can be tested, and the test results are averaged.

[0246] (2) Puncture strength test of isolation film

[0247] Puncture strength of barrier films is tested according to GB / T 36363-2018. The barrier film is cut into samples with a width of 10 mm and a length of 150 mm. A steel needle is used to puncture the barrier film at a rate of 50 mm / min. The maximum load at which the needle penetrates the barrier film is measured. Six or more barrier film samples can be tested, with three points measured for each sample and the average result calculated. The steel needle can have a diameter of 1 mm and a spherical tip radius of 0.5 mm. The surface of the steel needle must be smooth and free of rust, oxide layers, and oil stains.

[0248] (3) Ionic conductivity test of isolation membrane

[0249] The ionic conductivity of the isolation membrane was obtained by electrochemical impedance spectroscopy. Specifically, the isolation membrane was cut into discs with a diameter of 22 mm, dried, and placed between two stainless steel electrodes. After absorbing a sufficient amount of electrolyte, it was sealed to form a button battery, and an electrochemical impedance spectroscopy experiment was performed using an electrochemical workstation. The electrolyte salt of the electrolyte is LiDFOB with a concentration of 1.2 mol / L; the solvent of the electrolyte is a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a mass ratio of 30:70. The resistance Rs of different isolation membrane layers n was measured using the confined symmetric battery electrochemical impedance spectroscopy method as the isolation membrane resistance. The slope k (corresponding to the resistance of a single-layer isolation membrane) was obtained by plotting Rs and n. The ionic conductivity of the isolation membrane was calculated based on the resistance of the single-layer isolation membrane, the area of ​​the isolation membrane, and the thickness of the isolation membrane (single-layer thickness).

[0250] The electrochemical workstation can be a Shanghai Chenhua CHI 660C electrochemical workstation, with an AC signal frequency range of 0.01 Hz to 1 MHz and a sine wave potential amplitude of 5 mV. For accuracy, the average value of 6 parallel samples is taken as the test result.

[0251] The test results are shown in Table 2.

[0252] Next, the above-mentioned isolation membrane was assembled into a button-type battery, and the electrochemical performance was tested.

[0253] The button cell can be prepared as follows.

[0254] Lithium iron phosphate, conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed in an appropriate amount of N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1 to form a positive electrode slurry. The slurry was coated onto aluminum foil, the cathode current collector, and dried to form a positive electrode sheet. In an argon-protected glove box, the positive electrode sheet, separator, and lithium sheet were assembled into a CR2430 button cell. The electrolyte salt was LiDFOB at a concentration of 1.2 mol / L, and the solvent was a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 30:70.

[0255] The first coating layer of the separators in Examples 1-27 and Comparative Examples 1-3 all faced the lithium sheet, and the second coating layer all faced the positive electrode sheet. Comparative Example 4 used the same separator as Example 1, except that the first coating layer of the separator prepared in Example 1 was arranged to face the positive electrode sheet, and the second coating layer faced the lithium sheet.

[0256] At 25°C, charge the button cell at a constant current of 0.1C to 3.65V, then charge it at a constant voltage of 3.65V to 0.02C. After allowing the button cell to rest for 10 minutes, discharge it at a constant current of 0.1C to 2.5V. After cycling the button cell twice using the above method, perform the following cycling performance test.

[0257] First, charge the button battery at a constant current of 0.33C to 3.65V. Then, charge it at a constant voltage of 3.65V to 0.02C to fully charge the button battery. Then, after the button battery rests for 10 minutes, discharge it at a constant current of 0.33C to 2.5V. This is one cycle of charge and discharge. Record the discharge capacity at this time, which is the discharge capacity of the first cycle.

[0258] Cycle the button cell 100 times using the above method. Calculate the average coulombic efficiency of the button cell from the 21st to the 100th cycle as the average coulombic efficiency of the button cell. Coulombic efficiency = discharge capacity / charge capacity. Capacity retention of the button cell after 100 cycles = discharge capacity at the 100th cycle / discharge capacity at the 20th cycle.

[0259] The button battery was subjected to a cyclic charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded until the discharge capacity of the button battery decayed to 70% of the discharge capacity of the first cycle. The number of cycles at this time was used to characterize the cycle performance of the battery.

[0260] The test results are shown in Table 2.

[0261] Table 2

[0262] From Tables 1 and 2, it can be seen that by respectively arranging a first coating facing the negative electrode and a second coating facing the positive electrode on the two surfaces of the porous substrate, the first coating includes first particles (solid electrolyte), and the content of the first particles in the first coating is greater than 50 weight%, and the second coating includes second particles (inorganic particles that can react with lithium dendrites), and the content of the second particles in the second coating is greater than 50 weight%. The isolation membrane thus obtained can have both good mechanical strength and good ion conductivity.

[0263] It can be seen from Table 1 and Table 2 that the isolation membrane provided by the embodiments of the present application can enable the battery to have good cycle performance and can effectively reduce the probability of internal short circuit of the battery.

[0264] It can be seen from Tables 1 and 2 that when the first coating includes a small amount of third particles (inorganic particles that can react with lithium dendrites) in addition to the solid electrolyte, for example, no more than 10% by weight, the cycle performance of the battery can be further improved.

[0265] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical idea and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A separation film, wherein: The separator comprises a porous substrate and a first coating and a second coating respectively disposed on two surfaces of the porous substrate, wherein when used in a battery, the first coating faces the negative electrode and the second coating faces the positive electrode; The first coating layer includes first particles, the first particles include a solid electrolyte, and the content of the first particles in the first coating layer is greater than 50 wt %; The second coating layer includes second particles, the second particles include inorganic particles capable of reacting with lithium dendrites, and the content of the second particles in the second coating layer is greater than 50 weight %.

2. The isolation film according to claim 1, wherein: The content of the first particles in the first coating is greater than or equal to 60 wt %, optionally greater than or equal to 65 wt %, and more optionally 65-85 wt %; and / or, The content of the second particles in the second coating layer is greater than or equal to 60 wt %, and may be greater than or equal to 65 wt %, and may be more preferably 65-85 wt %.

3. The isolation film according to claim 1 or 2, wherein: The first coating further includes third particles; Optionally, the third particles include inorganic particles capable of reacting with lithium dendrites; and / or, Optionally, the content of the third particles in the first coating is greater than 0 and less than or equal to 10% by weight, and optionally greater than 0 and less than or equal to 5% by weight; and / or, Optionally, the volume distribution particle size Dv50 of the third particles is 0.05-3 μm, optionally 0.1-1 μm.

4. The isolation film according to any one of claims 1 to 3, wherein: The solid electrolyte includes an inorganic solid electrolyte; Optionally, the conductivity of the inorganic solid electrolyte is greater than or equal to 10 -7 S / cm, more preferably greater than or equal to 10 -4 S / cm.

5. The isolation film according to claim 4, wherein: The inorganic solid electrolyte includes one or more of an oxide-type inorganic solid electrolyte, a sulfide-type inorganic solid electrolyte and a halide-type inorganic solid electrolyte; Optionally, the oxide-type inorganic solid electrolyte includes one or more of a NASICON-type solid electrolyte, a garnet-type solid electrolyte, a perovskite-type solid electrolyte, and a LISICON-type solid electrolyte; and / or, Optionally, the sulfide-type inorganic solid electrolyte includes one or more of a sulfide-type crystalline solid electrolyte and a sulfide glass-type solid electrolyte.

6. The isolation film according to claim 4 or 5, wherein: The inorganic solid electrolyte includes lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate (Li x Al y Ge z (PO4)3, LAGP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate (Li x Al y Zr z (PO4)3, LAZP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum chromium phosphate (Li x Al y Cr z (PO4)3, LACP, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -type glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , LLZO), lithium lanthanum thallium oxide (Li5La3Ta2O 12 , LLTA), lithium zinc germanium oxide (Li 14 ZnGe4O 16 ), lithium thiargyrite electrolyte Li6PS5X (X includes one or more selected from Cl, Br, I), SiS2-type glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-type glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , and one or more of their respective doped compounds; optionally including lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, LATP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum germanium phosphate (Li x Al y Ge z (PO4)3, LAGP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum zirconium phosphate (Li x Al y Zr z (PO4)3, LAZP, 0 < x < 2, 0 < y < 1, 0 < z < 3), lithium aluminum chromium phosphate (Li x Al y Cr z (PO4)3, LACP, 0 < x < 2, 0 < y < 1, 0 < z < 3), and one or more of their respective doped compounds.

7. The isolation film according to any one of claims 1 to 6, wherein: The inorganic particles capable of reacting with lithium dendrites include inorganic ceramic particles; Optionally, the inorganic ceramic includes one or more of aluminum oxide, silicon dioxide, silicon nitride, ferric oxide, ferroferric oxide, cobalt monoxide, cobalt tetroxide, tin oxide, tin dioxide, nickel oxide, iron phosphate, copper oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, aluminum nitride, silicon nitride, boron nitride, zirconium titanate, barium titanate, and their respective modified materials. More preferably, the material may include one or more of aluminum oxide, silicon dioxide, silicon monoxide, cobalt monoxide, cobalt trioxide, tin monoxide, tin dioxide, nickel oxide, iron phosphate, copper oxide, titanium oxide, and their respective modified materials.

8. The isolation film according to any one of claims 1 to 7, wherein: The volume distribution particle size Dv50 of the first particles is 0.05-3 μm, and can be 0.1-1 μm; and / or, The volume distribution particle size Dv50 of the second particles is 0.5-5 μm, and can be optionally 1-3 μm.

9. The isolation film according to any one of claims 1 to 8, wherein: The first coating further comprises one or more of a first binder, a first dispersant, and a first thickener; Optionally, the mass ratio of the first particles to the first binder is 100:(1-25), more preferably 100:(5-22); and / or, Optionally, the mass ratio of the first particles to the first dispersant is 100:(1.0-3.5), more preferably 100:(1.2-2.5); and / or, Optionally, the mass ratio of the first particles to the first thickener is 100:(10-30), and more preferably 100:(12-26).

10. The isolation film according to claim 9, wherein: The first binder includes one or more of vinylidene fluoride homopolymer and / or copolymer, sodium carboxymethyl cellulose, and styrene-butadiene rubber; and / or, The first dispersant comprises one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymer, polyester block copolymer, polyethylene glycol type polyol, polyethylene imine, and their respective derivatives; and / or, The first thickener includes one or more of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose, polyacrylate, polyurethane, and polyether.

11. The isolation film according to any one of claims 1 to 10, wherein: The second coating further comprises one or more of a second binder, a second dispersant, and a second thickener; Optionally, the mass ratio of the second particles to the second binder is 100:(1-25), more preferably 100:(8-22); and / or, Optionally, the mass ratio of the second particles to the second dispersant is 100:(0.5-4.0), more preferably 100:(1.0-2.0); and / or, Optionally, the mass ratio of the second particles to the second thickener is 100:(5-30), and more preferably 100:(10-25).

12. The isolation film according to claim 11, wherein: The second binder includes one or more of vinylidene fluoride homopolymer and / or copolymer, sodium carboxymethyl cellulose, and styrene-butadiene rubber; and / or, The second dispersant comprises one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymer, polyester block copolymer, polyethylene glycol type polyol, polyethylene imine, and their respective derivatives; and / or, The second thickener includes one or more of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, polyacrylate, polyurethane, and polyether.

13. The isolation film according to any one of claims 1 to 12, wherein: The surface density of the first coating is 9-12 g / m 2 , optional 10-11.5g / m 2 and / or, The surface density of the second coating is 4-14 g / m 2 , optional 8-12g / m 2 .

14. The isolation film according to any one of claims 1 to 13, wherein: The ratio of the thickness of the first coating layer to the thickness of the second coating layer is (0.2-5):1, and can be optionally (0.25-4):

1.

15. The isolation film according to any one of claims 1 to 14, wherein: The thickness of the first coating is 1-7 μm, and can be 1.5-6 μm; and / or, The thickness of the second coating is 1-7 μm, and can be 1.5-6 μm; and / or, The total thickness of the isolation film is 8-25 μm, and can be 8-18 μm.

16. The isolation film according to any one of claims 1 to 15, wherein: The porous substrate comprises one or more of polyolefins, halogenated polyolefins, polyamides, polyesters, and their respective derivatives; and / or, The thickness of the porous substrate is 4-15 μm, and can be 5-10 μm.

17. The isolation film according to any one of claims 1 to 16, wherein: The isolation film satisfies at least one of the following: (1) The porosity of the isolation membrane is 40%-80%, and can be 45%-70%; (2) The transverse tensile strength of the isolation film is 1000-1500 kgf / cm 2 , optional 1100-1300kgf / cm 2 ; (3) The peel strength between the first coating layer of the isolation film and the porous substrate is 8.9-13.2 N / m, and can be 9.1-11.8 N / m; (4) The peel strength between the second coating layer of the isolation film and the porous substrate is 12.9-20.6 N / m, and can be 13.5-17.8 N / m; (5) The puncture strength of the isolation film is 9.60-11.50 N·μm -1 , optional: 9.80-10.90N·μm -1 ; (6) The ionic conductivity of the isolation membrane at 25°C is 1.40-2.50 mS·cm -1 , optional: 1.60-2.15mS·cm -1 .

18. A battery comprising a battery cell and a casing, wherein the battery cell comprises a positive electrode sheet, a negative electrode sheet and the isolation membrane according to any one of claims 1 to 17, wherein the first coating of the isolation membrane faces the negative electrode sheet, and the second coating of the isolation membrane faces the positive electrode sheet.

19. The battery according to claim 18, wherein The battery cell includes at least one of a lithium-ion battery cell, a lithium metal battery cell, a negative electrode-free lithium metal battery cell, a lithium-sulfur battery cell, and a lithium-air battery cell.

20. An electrical device comprising the battery according to claim 18 or 19.